2021
DOI: 10.1002/ehf2.13645
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors and cardiac remodelling: a systematic review and meta‐analysis of randomized cardiac magnetic resonance imaging trials

Abstract: Aims Recent large randomized controlled trials (RCTs) have demonstrated efficacy of sodium‐glucose cotransporter‐2 inhibitors (SGLT2i) in both preventing and treating heart failure (HF). SGLT2i‐induced reversal of left ventricular remodelling has been proposed as a mechanism contributing to this effect. Methods and results We performed a systematic review and meta‐analysis of RCTs to compare SGLT2i versus placebo (treatment duration >3 months) on cardiac remodelling parameters as measured by cardiac magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 19 publications
3
44
0
4
Order By: Relevance
“…A meta-analysis of three cardiac magnetic resonance imaging trials reported that SGLT2i therapy in patients with HFrEF was not significantly associated with reverse cardiac remodeling, including left ventricular ejection fraction, end-systolic volume, and end-diastolic volume; however, there was a tendency toward the improvement of these parameters ( 42 ).…”
Section: Pharmacological Treatment For Dynamic Smrmentioning
confidence: 99%
“…A meta-analysis of three cardiac magnetic resonance imaging trials reported that SGLT2i therapy in patients with HFrEF was not significantly associated with reverse cardiac remodeling, including left ventricular ejection fraction, end-systolic volume, and end-diastolic volume; however, there was a tendency toward the improvement of these parameters ( 42 ).…”
Section: Pharmacological Treatment For Dynamic Smrmentioning
confidence: 99%
“…The meta-analyses, which have been previously reported, have demonstrated controversial data regarding cardiac protection and the possibility to reverse adverse cardiac remodeling. Indeed, Yu et al (2021) [33] did not find strong evidence that SGLT2 inhibitors influence ACR parameters, such as LV mass index, LV enddiastolic and end-systolic volume indexes, or left atrial volume index; however, the beneficial changes in the E/e' ratio, biological markers (e.g., NT-pro brain natriuretic peptide) and quality of life have been concisely determined. In addition, SGLT2 inhibitors appeared to be significantly effective in LV ejection fraction increase solely among patients with HFrEF.…”
Section: Meta-analyses Of Clinical Studies Devoted To Sglt2 Inhibitor...mentioning
confidence: 99%
“…Гипертрофия, фиброз и воспаление миокарда приводят к ремоделированию сердца при ХСН, которое признается основным фактором, определяющим ее тяжесть [50]. ИНГК2 уменьшали ремоделирование миокарда у пациентов с СД 2-го типа и гипертрофией левого желудочка, но не у больных с ХСН [51]. Это повышает вероятность прямого кардиотропного эффекта ИНГК2 при ХСН за пределами снижения нагрузки на желудочки и влияния на ремоделирование миокарда.…”
Section: современные представления о механизмах эффективности ингибит...unclassified
“…Объединенный анализ данных об участниках исследований DAPA-HF и DAPA-CKD без СД (n = 4 003) показал, что лечение дапаглифлозином снижает заболеваемость впервые выявленным СД 2-го типа [63]. Эффект, подобный влиянию метформина, на профилактику СД 2-го типа отмечался без изменения уровня гемоглобина A1c, что 2022;16 (17): [44][45][46][47][48][49][50][51] Хроническая сердечная недостаточность свидетельствует не о маскировке гипергликемии гипогликемизирующим препаратом, а о существенном влиянии на патогенез СД, возможно, улучшении функции β-клеток или усилении чувствительности к инсулину.…”
Section: дапаглифлозин или эмпаглифлозин -какой препарат предпочтител...unclassified
See 1 more Smart Citation